Women Have Equal Right to Get Their Voices Heard As Men in the Novel of Kamala Markandaya with Special Reference to Nectar in a Sieve: Exploring Female Identity in Kamala Markandaya's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Indian novelists in English have presenting woman as the centre of concern in their novels. A woman’s search for identity is a recurrent theme in their fiction. Kamala Markandaya is one of the finest and most distinguished Indian novelists in English of the post-colonial era who is internationally recognized. She has achieved a world-wide distinction by winning Asian prize for her literary achievement in 1974.